DUALISM OF IDENTITY IN JEN WANG'S “THE PRINCE AND THE DRESSMAKER” - Sari, Dian Eka; Ayu, Fransiska Tri (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
Exercising freedom of choice must always be accompanied by responsibility. However, freedom is never absolute, as it is bounded by facticity arising from social conditions, relationships with others, and existing norms. This research examines Jen Wang’s The Prince and the Dressmaker, which depicts Prince Sebastian’s dual identity as both a royal heir and his alter ego, Lady Crystallia. As the sole heir to the throne, Prince Sebastian is expected to uphold traditional norms, social expectations, and royal duties imposed by society. Despite these constraints, he chooses to express himself as Lady Crystallia at night, wandering the city and exploring fashion as a form of self-expression. This choice reflects his freedom while simultaneously revealing the limitations imposed by his social position and responsibilities. The study demonstrates that morals, norms, and rules are not intended to eliminate individual freedom but to emphasize that one person’s freedom is shaped and limited by the freedom of others. Drawing on Sartre’s existentialist concepts—such as absurdity, the look, authenticity, meaning, and bad faith—this research reveals Prince Sebastian’s divided existence. Ultimately, he embodies two identities: one constrained by societal norms and another representing his pursuit of authenticity and meaning in life.